2010
DOI: 10.1186/1471-2377-10-93
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rifampicin and clindamycin impregnated devices against Staphylococcusspp. infection after cerebrospinal fluid diversion procedures

Abstract: BackgroundInfection is a major complication of cerebrospinal fluid shunting procedures. The present report assesses the efficacy of such catheters in both shunts and external ventricular drains (EVDs) against infection and particularly against Staphylococcus spp. infection.MethodsAll shunt and EVD procedures performed by means of antibiotic-impregnated catheters (AICs) and non-AICs during the period of study were registered. In cases of shunt procedures, a minimal follow-up of 90 days was considered, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Although 2 earlier studies did not find any effect on infection rates from AIS catheter use, 11,21 larger studies, including meta-analyses, have reported a reduction largely in line with that reported in the present study. 2,[7][8][9][10][12][13][14][15][16][17]20,22,24,28 This study supports previous recommendations made in favor of universal adoption of AISs. There is increasing evidence that, in addition to improvement in clinical outcome, there are strong economic and cost-effectiveness arguments for the use of AIS catheters.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although 2 earlier studies did not find any effect on infection rates from AIS catheter use, 11,21 larger studies, including meta-analyses, have reported a reduction largely in line with that reported in the present study. 2,[7][8][9][10][12][13][14][15][16][17]20,22,24,28 This study supports previous recommendations made in favor of universal adoption of AISs. There is increasing evidence that, in addition to improvement in clinical outcome, there are strong economic and cost-effectiveness arguments for the use of AIS catheters.…”
Section: Discussionsupporting
confidence: 80%
“…2,[7][8][9][10][11][12][13][14][15][16][17][20][21][22]24,28 These studies are somewhat heterogeneous in terms of follow-up, patient population (pediatric only, adult only, or mixed), whether primary insertion only or revision surgeries also were included, and in reporting of causative pathogens. Some recent studies have highlighted the possibility of AIS catheters promoting selection of antibiotic-resistant organisms.…”
mentioning
confidence: 99%
“…Five studies were conducted in children and in adult populations. 16,21,22,24,25 A random model was used because of statistically high heterogeneity between studies (c 2 ¼ 10.45; P ¼ .03; I 2 ¼ 62%), and the value of RR was 0.31 with a significant benefit in favor of AI-EVD catheters (95% CI, 0.14-0.67; P ¼ .003) (Fig 5B). The pooled data from all 10 studies showed a significant difference (RR, 0.31; 95% CI, 0.18-0.55; P < .0001), but statistically significant moderate heterogeneity was observed between the studies (c 2 ¼ 18.09; P ¼ .03; I 2 ¼ 50%).…”
Section: Ai-evd Vs Plain Evd Cathetersmentioning
confidence: 99%
“…The characteristics of the included studies are summarized in Table 1 and Table 2. 16,[18][19][20][21][22][23][24][25][26][27][28][29][30] Ten studies compared AI-EVD catheters with plain EVD catheters, of which 3 were RCTs. Five studies compared SI-EVD catheters with plain EVD catheters, but only 1 study was an RCT.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…4,6,37 Many studies have evaluated the efficacy of AISs compared with standard shunts (SSs) in the prevention of shunt infections, including two recent systematic reviews and meta-analyses. 1,2,15,17,[19][20][21]24,27,28,31,35,36,38,44,45,50,51,53 The purpose of this evidence-based review is to examine data on the use of AISs and SSs and compare these treatments in the prevention of shunt infections in the pediatric population.…”
mentioning
confidence: 99%